L-Asparagine on strontium hydroxyapatite nanorods morphology and biocompatibility. (13th August 2009) - Lam, Raymond Wing Moon; Wong, Chi Tak; Li, Zhao Yang; Luk, Keith Dip Kei; Cheung, Kenneth; Chiu, Peter; Xu, Bing; Chan, Wai; Fang, David; Leong, John; Lu, William
In this study, we investigated the influence of L-Asparagine (L-Asn) on strontium hydroxyapatite (Sr-HA) nanorod morphology and their biocompatibility. Ammonia was used to adjust the pH of L-Asn Sr-HA precursor and was heated at 80-120°C for 5-15 h. From Transmission Electron Microscopy's (TEM) images, the lengths and diameters of the nanorod were 0.3901 ± 0.0804 µm and 30.4 ± 4.6 nm, respectively. L-Asn Sr-HA phosphate system provides a high phase purity of monodispersed strontium hydroxyapatite nanorod. From Live/Dead Assay, L-Asn Sr-HA nanorod showed cell-dependent cytotoxicity (SaOS-2 < C2C12 < L929) and these results have shown L-Asn Sr-HA nanorod can be adopted as fibrous tissue formation inhibitor.